2015
DOI: 10.3928/01477447-20150204-04
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Nerve Wrap for Median Nerve Scarring

Abstract: Nerve wrapping materials have been manufactured to inhibit nerve tissue adhesions and diminish inflammatory and immunologic reactions in nerve surgery. Collagen nerve wrap is a biodegradable type I collagen material that acts as an interface between the nerve and the surrounding tissues. Its main advantage is that it stays in place during the period of tissue healing and is then gradually absorbed once tissue healing is completed. This article presents a surgical technique that used a collagen nerve wrap for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…To overcome this problem, collagen materials have recently been developed as an alternative to autologous veins . Vein wrapping was first employed in the upper extremity to avoid scarring in peripheral nerve injury .…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…To overcome this problem, collagen materials have recently been developed as an alternative to autologous veins . Vein wrapping was first employed in the upper extremity to avoid scarring in peripheral nerve injury .…”
mentioning
confidence: 99%
“…These studies suggested that collagen materials supplemented with trophic factors may be promising for recurrent compressive neuropathy not amenable to autologous vein wrapping. Collagen materials have since been developed as an alternative to autologous veins and to similarly decrease nerve scarring and improve nerve gliding …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Collagen nerve wraps maintain nerve mobility following neurolysis. 38,39) All five surgical exposures required neurolysis of the PCBMN. In one patient the nerve was in continuity and neurolysis resolved the problem satisfactorily.…”
Section: )mentioning
confidence: 99%